2004
DOI: 10.1021/jp037911q
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Phase Diagram of Complex Block Copolymers:  ABC Star Triblock Copolymers

Abstract: Microphases and triangle phase diagrams of ABC star triblock copolymers are investigated on the basis of a real-space implementation of the self-consistent field theory (SCFT) for polymers. For the sake of numerical tractability, the calculations are carried out in two dimensions (2D). Nine stable microphases are uncovered, including hexagonal lattice, core−shell hexagonal lattice, lamellae, and lamellae with beads at the interface as well as a variety of complex morphologies that are absent in linear ABC trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
152
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(168 citation statements)
references
References 27 publications
15
152
1
Order By: Relevance
“…We found that these linear and star-shaped ABC terpolymers self-assemble into lamellar phases when using these parameters (Figure 3). The calculations agree with those of Yang et al [18,19] In our simulation, we select the relative deformation from À0.15 to + 0.15, and the corresponding free energies (the free energy of extension or shear) are calculated. Table 1 lists the dimensionless tensile moduli, obtained from Equation (17) for the triblock copolymer system, of lamellar structures having different molecular architectures (linear and star).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We found that these linear and star-shaped ABC terpolymers self-assemble into lamellar phases when using these parameters (Figure 3). The calculations agree with those of Yang et al [18,19] In our simulation, we select the relative deformation from À0.15 to + 0.15, and the corresponding free energies (the free energy of extension or shear) are calculated. Table 1 lists the dimensionless tensile moduli, obtained from Equation (17) for the triblock copolymer system, of lamellar structures having different molecular architectures (linear and star).…”
Section: Resultssupporting
confidence: 81%
“…Based on theoretical studies, linear and starlike block copolymers can assemble into similar ordered microstructures when their components and interaction energies between blocks are nearly identical. [18,19] Our focus in this investigation is to study the influence of the block copolymer architecture on the tensile properties of polymeric nanomaterials having lamellar phases.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial differences distinguishing LSO and ostensibly similar ISO/SIO triblocks could potentially be attributed to either the polymer architecture (brush vs. linear) or block-block interactions. We note that architecture-induced segmental mixing has been demonstrated in ABC heteroarm star terpolymers, wherein forming low-energy morphologies may force one arm to transit across an incompatible domain (χ > 0) (45,46). However, these architecture effects do not pertain to brush LSO because the blocks are connected end-to-end in the same way as linear ABC triblock terpolymers.…”
Section: Resultsmentioning
confidence: 85%
“…This theoretical work has been further completed by Tang et al [105,106], Tyler et al [107,108], and more recently by Chen and Xia [109] by using selfconsistent field theory simulations. Playing with the flexibility/rigidity of the polymer segments, various new morphologies could be discovered and some of them have been confirmed experimentally [110][111][112].…”
Section: Bulk Morphologiesmentioning
confidence: 98%